2017
DOI: 10.1177/0300060517710584
|View full text |Cite
|
Sign up to set email alerts
|

INTERTAN nail versus proximal femoral nail antirotation-Asia for intertrochanteric femur fractures in elderly patients with primary osteoporosis

Abstract: ObjectivesTo compare the long-term functional and radiographic outcomes of the proximal femoral nail antirotation-Asia (PFNA-II) and INTERTAN nail (IT) in the management of intertrochanteric femoral fractures (IFFs) (AO/OTA Type 31A1.1-A2.3) in elderly patients with primary osteoporosis.MethodsA retrospective comparative study was performed in our institution. From January 2009 to March 2012, 243 patients with osteoporosis (243 hips) with IFFs (AO/OTA Type 3.1A1.1-A2.3) underwent repair with either a PFNA-II o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 27 publications
2
43
2
Order By: Relevance
“…HHS tends to improve in the first six months, tends to plateau between six to nine months and then starts deteriorating gradually even below the values achieved at one month postoperatively. Long term functional outcome studies on HHS in pertrochanteric fractures have shown that HHS value at 36 months postoperatively was lower than the HHS at one month postoperatively 4 . Frihagen et al, 5 described the responsiveness of HHS in elderly patients (mean age -83 years) with intracapsular neck of femur fracture and treated with either internal fixation or hemiarthroplasty.…”
Section: Responsivenessmentioning
confidence: 96%
See 1 more Smart Citation
“…HHS tends to improve in the first six months, tends to plateau between six to nine months and then starts deteriorating gradually even below the values achieved at one month postoperatively. Long term functional outcome studies on HHS in pertrochanteric fractures have shown that HHS value at 36 months postoperatively was lower than the HHS at one month postoperatively 4 . Frihagen et al, 5 described the responsiveness of HHS in elderly patients (mean age -83 years) with intracapsular neck of femur fracture and treated with either internal fixation or hemiarthroplasty.…”
Section: Responsivenessmentioning
confidence: 96%
“…The HHS was initially described for assessment of functional outcome after mold arthroplasty for posttraumatic arthritis 1 . The HHS has been used to evaluate functional outcome after pertrochanteric hip fracture [2][3][4] and intracapsular fracture neck of femur 5 .Construct validity of an outcome instrument shows that all the domains of the instrument are indeed measuring what they are supposed to measure. Responsiveness of an outcome instrument is defined as the sensitivity of the instrument to detect clinically relevant change over a period of time 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The search yielded 308 potentially relevant reports, and 117 remained after the duplicate articles were deleted, of which 57 were excluded by preliminary screening; further careful screening of the full text excluded 51 articles leaving 9 for detailed evaluation. Nine studies ( n = 1332 patients) are published between January 2013 and December 2019 that fulfilled the inclusion and exclusion criteria, including 2 RCTs and 7 observational studies [ 14 , 20 27 ]. A total of 1332 patients were relatively evenly distributed in PFNA ( n = 681 patients) and InterTAN nail groups ( n = 651 patients), and the proportion of the two surgical procedures in A1, A2, and A3 fractures is 88/80, 479/460, and 113/112, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al. 17 reported 174 patients with osteoporotic AO/OTA 31-A2 IHFs who received treatment of PFNA or IT. They found that the rate of periprosthetic fractures was 1.1% or 0%, respectively (P = 1.000).…”
Section: Discussionmentioning
confidence: 99%